A AUTORIA NA ERA DO CHATGPT: UMA REFLEXÃO À LUZ DAS IDEIAS DE FOUCAULT - SOUZA, PAULO SÉRGIO DA SILVA (2024)
This paper aims to reflect upon the conception of authorship in the era of ChatGPT from Foucault’s perspective (1969; 1972; 1987; 1999; 2000; 2001). We explore the transformations in the concept of authorship amidst the growing presence of artificial intelligence, investigating ethical and legal challenges, as well as the dynamics of collaborative writing between humans and machines. Employing a bibliographical approach, the study is grounded chiefly in Foucault’s ideas on power and authorship, but also addresses Vygotsky’s concept of the Zone of Proximal Development. The discussion unveils ChatGPT’s influence on textual production, emphasizing the importance of understanding and regulating the interaction between human and automated authors, including its use in educational settings and for academic purposes. To illustrate the points presented in the paper, we have included an interview conducted using ChatGPT. It is concluded that artificial intelligence, as represented by ChatGPT, challenges traditional concepts of authorship, necessitating ongoing reflection on the ethical, legal, and practical impacts of this new reality in text production. Finally, this paper offers a critical reflection on authorship in the era of ChatGPT, exploring its potentialities and limitations, and provoking thoughts on the role of technology in the creative process and the construction of discourses.